Social representations of sexuality developed by women in the context of Aids - Solange Gurgel Alexandre; Maria Lúcia Duarte Pereira; Raquel Santos Monte; Eysler Gonçalves Maia; Jemima Samela Marques Barbosa; Sammya Karla Borges Moura (Rev Rene)
This study aimed to understand the social representations of sexuality, developed by women aged 50 and older with or without HIV/AIDS. This was a research with qualitative approach, based on Social Representations Theory, carried out in Fortaleza-CE, Brazil, with 44 women, 22 diagnosed with and 22 diagnosed without HIV/AIDS. We used the techniques of semi-structured interview and non-systematic observation. Data were submitted to content analysis and two main categories were verified: concepts on HIV/AIDS and experiences of sexuality. The results showed that for the women living with the disease there was a mix of anxiety, stigma, socioeconomic difficulties, disruption of emotional bonds, guilt and fear. Among women diagnosed without, a low perception of the risk of acquiring the infection and the fear of discovering the seropositivity, come from the misinformation on the disease. Studies on the issues of HIV/AIDS infection in women aged 50 and older should be widely encouraged, in order to support the development of actions and prevention programs addressed to this population.